Faktor-Faktor yang Mempengaruhi Kebiasaan Jajan Siswa-Siswi terhadap Kejadian Diare Akut - Sri Lestari Ramadhani Nasution; Tan Suyono; Ermi Girsang; Ayu Anggraini Bangun (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the factors influencing students' snacking habits on the incidence of acute diarrhea. The method used is a cross-sectional survey with an explanatory research approach. The results showed that there was an effect of attitude (p = 0.024), trust (p = 0.007), availability of snacks (p = 0.012), peers (p = 0.013), the role of the family on acute diarrhea (p = 0.021), but there was no effect the amount of pocket money (p = 0.466) and the role of the mass media in acute diarrhea (p = 0.0869). In conclusion, attitudes, beliefs, availability of snacks, peers and the role of the family affect acute diarrhea, while the amount of pocket money and the role of the mass media do not affect acute diarrhea. Keywords: School Age Children, Acute Diarrhea, Snacking Habits